Thermal properties of polyethylene-grafted sheetlike silsesquioxanes - Sharma, Vivek; Paulbudhe, Uday; Gupta, Poonam; Zalte, Akshat Shirish; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2025)
Polyethylene-grafted layered silsesquioxanes, termed polyethylene-clays (PEC), are nanocomposites comprising polyethylene chains tethered to inorganic sheets with a phyllosilicate-like structure. Here, we report that these nanocomposites show two-stage crystallization on cooling, qualitatively different from previous reports on polyethylene nanocomposites. We employ differential scanning calorimetry (DSC) and small-angle X-ray scattering (SAXS) to study the melting and crystallization of PEC. End tethering of the polyethylene chains to a nanosheet strongly influences the manner in which PEC crystallizes from the melt on cooling. PEC exhibits two-step crystallization, characterized by a sharp high-temperature exotherm, followed by a broader exotherm at lower temperatures, in contrast to a single sharp exotherm for neat polyethylene. SAXS indicates that lamellar stacks form at high temperatures and that the low-temperature exotherm corresponds to the formation of additional lamellae and their insertion within these stacks. PEC exhibits lower peak melting temperature, lower crystallinity, and a wider melting range relative to polyethylene. We show that the progress of crystallization of PEC is determined by its ultraslow relaxation dynamics. In contrast, PEC in xylene solution exhibits a significantly shorter relaxation time than the melt PEC. Such systems exhibited a single exotherm on cooling and SAXS structure factor peaks with peak positions in a ratio of 1:2. We hypothesize that the high melt viscosity inhibits the crystallization-induced decrease in the specific volume of PEC, resulting in tensile internal stresses that determine the observed thermal behavior.
Keywords: clay; Crystallization; Nanocomposite; Polyethylene; silsesquioxane